Penegakan Hukum Larangan Berburu Satuan Liar di Wilayah TNK Labuan BAJO Manggarai Barat - Fransiskus Leric Kleden; Ida Ayu Putu Widiati; I Wayan Arthanaya (Jurnal Konstruksi Hukum, 2021)
The diversity of fauna in Indonesia is Yaranus komodoensis in the Komodo National Park (TNK) Labuan Bajo, East Nusa Tenggara. Currently, Kornodo is suspected of experiencing local extinction, thought to be caused by a reduced deer population due to illegal hunting, law enforcement on the prohibition of hunting wildlife in the area is still ineffective considering that hunting of wild animals is still happening. Efforts are made to increase the effectiveness of law enforcement on wildlife hunting by socializing the community and increasing the number of forest police officers in each region. . The research method used is empirical legal research, meaning that a study examines the problem based on the facts that occur in the field. From the research, there was hunting of deer wildlife in Komodo National Park. The purpose of this research is to determine the enforcement of the law on the prohibition of hunting wildlife in the Kornodo National Park and to find out the effectiveness of enforcing the law on the prohibition of hunting wildlife in the Komodo National Park.